Studi Tafsir Tematik Ayat Al-Qur’an tentang Ibrah Peringatan Allah untuk Bani Israil - Raihan Sabdanurrahmat; Dadan Rusmana (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study is to discuss the ibrah verses of Allah's warning to the Bani Israil. This research is a qualitative research with a literature study method that focuses on content analysis of research sources. The results and discussion of this study show a musasabah relationship between the warning keywords and other vocabulary in the verses regarding warnings. The conclusion of this study is that there is ibrah in the verses concerning the warning to the Bani Israil, namely the leveraging of goodness and pleasure before the commandment verse is that Allah intends to bring up the bad habits of humans. In addition, the leveraging of this goodness will pressure people to do what they are told. This research resulted in many research gaps that require further research, namely the problem of using words for warning whether using different warning words will result in different interpretations of the verse.